Demokrasi Liberal Vs Demokrasi Indonesia - Sidratahta Mukhtar; Utoyo Harjito; Afrianti Wulandari Rakhmayanti (Novateur Publications, 2022)
The democratization process in Indonesia in the last two decades has led our political system to lead to liberal democracy. Whereas as a country resulting from a national revolution, Indonesia has national thoughts and ideologies which are products of state history and practice. Founding father, Dr. Ir. Soekarno said that Indonesian nationalism was built from knowledge, humanity through the synergy between nationalism, Islamism and Marxism. Each nation has its own way of fighting, has its own characteristics. (Soekarno, 1958). The main problem raised in this study is what is the right model of democracy for Indonesia? The method used is a qualitative approach by prioritizing the study of thoughts and analysis of various views, theories and concepts of democracy in modern Indonesia. The theories and concepts used refer to the following theories/concepts: Anthony Smith, Renan, Bill Liddle, Vedi R Farid. Based on this study, it can be concluded that Indonesia is undergoing a transformation from an authoritarian political system and a liberal democratic system to a political system that is the Indonesian model. Therefore, the discussion of parties and democracy that is built will not only give birth to modernization and the party system but at the same time give birth to the substance of democracy, namely justice and welfare
Keywords: demokrasi, ideologi, founding father.